Analysis Of Grease Degradation Under Elastohydrodynamic Lubricant - Abdul Mutalib, Nurul Rafika Amira (Universiti Sains Malaysia, 2022)
The performance of grease is important as it may influence the friction and wear of the lubricated components. The purpose of this study is to investigate the performance and degradation of the grease in rolling contact applications. In this study, four types of grease has been studied, there are palm oil with Cu nanoparticle grease, palm oil with MoS2 micro particle, SKF LGGB 2/0.4 mineral Grease and BIOGREASE Food Grade Grease Marlin-9. ASTM D2266 Standard were used to study the wear preventive characteristic of the lubricating grease. The grease performance at high temperature and load with the value of 100℃ and 100kg are also evaluated. DUCOM Four-Ball Tester Machine, Hitachi TM1000-Tabletop Microscope machine, Hitachi S 3400N SEM, Alicona IFM-Optical 3D surface metrology and Thermogravimetric Analyzer Pyris 1 (Perkin Elmer) were used in this study to analyse the grease performance and degradation. The finiding shown that the performance of the palm oil grease with additive is comparable to the commercial mineral grease. At high temperature and load test, the palm oil with Cu and MoS2 additive show low and stable COF values, and this indicates that no degradation occurs to the grease when operating at high temperature and load. These grease also show the best performance at high load application with a small roughness and wear depth profile. LGGB has the best tribology perfomance in all aspect and this is undeniably because it a commercial grease that has been used all over the world. Food Grade has the worst performance because this type of grease is widely used in the food line operation. To prevent harm to human, the formulation ingredients must be safe to human but at the same time can protect the machine.